2012
DOI: 10.1038/ajh.2012.99
|View full text |Cite
|
Sign up to set email alerts
|

Association of Frailty Syndrome in the Elderly With Higher Blood Pressure and Other Cardiovascular Risk Factors

Abstract: Subjects with frailty syndrome had higher BP evaluated by ABPM and other cardiovascular risk factors such as lower HDL and more abdominal fat than nonfrailty group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 23 publications
7
49
1
3
Order By: Relevance
“…32,33 Another point that should be taken into consideration is sarcopenic obesity, which consists of increased levels of adipose tissue relating to the ageing process, regardless of BMI, with higher deposition of visceral fat and muscle infiltration. 34 Concerning the absence of association of LDL and triglycerides with the condition of pre-frailty, another Brazilian study 9 also found similar results, in which LDL (P = 0.52) and triglycerides (P = 0.65) did not present differences. A prospective investigation in Finland 35 found similar percentages, without significant differences (P = 0.45) in triglyceride and frailty levels.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…32,33 Another point that should be taken into consideration is sarcopenic obesity, which consists of increased levels of adipose tissue relating to the ageing process, regardless of BMI, with higher deposition of visceral fat and muscle infiltration. 34 Concerning the absence of association of LDL and triglycerides with the condition of pre-frailty, another Brazilian study 9 also found similar results, in which LDL (P = 0.52) and triglycerides (P = 0.65) did not present differences. A prospective investigation in Finland 35 found similar percentages, without significant differences (P = 0.45) in triglyceride and frailty levels.…”
Section: Resultssupporting
confidence: 66%
“…Cardiovascular risk factors such as BMI, low-density lipoprotein (LDL) levels, total cholesterol and triglycerides were not associated with frailty. 9 In a study carried out among hospitalized elderly people, BMI and arterial systemic hypertension were not associated with frailty syndrome. 10 Thus, the findings from studies conducted in Brazil and in other countries are contradictory, which highlights the need for more studies in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of the criteria varies according to the population studied, although weakness characterized by low handgrip strength has been the most prevalent criterion in many studies, underscoring the importance of muscle strength in the genesis of the syndrome. [27][28][29] In an investigation on the early manifestations and development of frailty phenotype in women, Xue et al reported that the incidence of frailty among women who were non-frail at the beginning of the study was 9%. 29 Despite the heterogeneity observed, weakness was the most common initial manifestation and its occurrence together with slowness and low physical activity preceded exhaustion and weight loss in 76% of the women who were not frail at the beginning of the study.…”
Section: And 87% In Belomentioning
confidence: 99%
“…Another issue requiring clarification is the effectiveness of interventions in terms of drug prescription and changes in analytical parameters. 25,26 The focus of attention should also be directed to economic data, namely, costs relative to benefits and/or savings associated with implementing the interventions for pre-frailty and frailty. 27 A preliminary search of the JBI Database of Systematic Reviews and Implementation Reports, the Cochrane Database of Systematic Reviews, Prospero, CINAHL, and Medline has revealed that there are currently no systematic review (neither published nor in progress) on clinical/medical and economic effectiveness of interventions to prevent or reduce frailty in older adults.…”
Section: Introductionmentioning
confidence: 99%